The Effectiveness of Manual Acupuncture Therapy for Acne Vulgaris: A Case Report - Diana Marsha Fredy; Irma Nareswari (Faculty of Medicine, University of Jember, 2022)
Acne vulgaris (AV) is a chronic inflammation of pilosebaceous glands. The clinical presentation of AV can be described as an inflammatory lesion and non-inflammatory lesions. The diagnosis of AV is through clinical evaluations. AV was graded according to clinical severity using Lehmann’s criteria. AV predilection most commonly appears on the face, chest, and back. AV causes the greatest burden between 10 to 30 years old and can cause anxiety and decrease self-confidence, instigating decreased quality of life. Acupuncture is a non-pharmacological treatment modality that is performed using filiform needles at acupuncture points. An 18-year-old woman was diagnosed with a moderate degree of AV based on Lehmann's criteria. She received manual acupuncture acupoints with the needles retained for 30 minutes. The treatment was conducted 2 times a week for a total of 12 treatments. After 12 treatments of acupuncture therapy, the degree of AV was reduced from moderate to mild, with an 81.25% reduction in total lesions. Follow-up was carried out 1 month after the treatment, showing that the effect of acupuncture remained. The acupuncture mechanism works directly on acne lesions by improving microcirculation, reducing proinflammatory reactions, and increasing anti-inflammatory, as well as regulating the HPA axis which can reduce stress and improve hormones. Manual acupuncture can be considered a non-pharmacological therapeutic modality to treat AV with minimal side effects.